Extranodal NK/T-cell lymphoma, nasal type: a case report - Ramos, Arely L. G.; Lessa, Camila O.; García, Mónica M. P.; Eleuterio, Sarahi A. (International Journal of Research in Medical Sciences, 2025)
Extranodal NK/T-cell lymphoma, nasal type (ENKTL-NT), is a rare and aggressive malignancy associated with Epstein-Barr virus (EBV). Its clinical presentation includes midfacial destruction, ulceration, and nasal obstruction, often leading to misdiagnosis. A 43-year-old male presented with a rapidly progressive nasal lesion. Clinical evaluation, imaging, and histopathological analysis with immunohistochemistry confirmed ENKTL-NT. Treatment includes radiotherapy and chemotherapy, improving survival rates, though prognosis remains poor in advanced cases. Early diagnosis is crucial for better outcomes.